Do terror attacks affect the Euro? Evidence from the 21st century - Stelios Markoulis (Journal of Risk and Financial Management, 2021)
The objective of this paper is to examine whether terror attacks that took place in the Eurozone in the 21st century had a significant effect on the price of the Euro. Its novelty is twofold: it is the first study that assesses the impact of such events on the price of the Euro and employs a relatively large number of these events. The event-study methodology is used to deduce whether, after a terror event, the value of the Euro declines vs. other major currencies. We found that it does not, since following such an event, the decline was seldom over 0.5%. We also found, however, evidence of some diversion to safe-haven currencies, such as the Swiss Franc. Regression analysis revealed that factors such as the "number of attacks", the "type of target" and the "type of attack", but not the number of casualties, affected the price of the Euro.
Keywords: 330; Euro; event-study methodology; foreign exchange market; market reaction; terrorism